Investigation on the Different Needs of Practicing Doctors for Continuing Medical Education under the Three-Level Medical System in China - Hanbi Wang; Aijun Sun; Zhiyuan Zhang; Jie Chen; Han Dong; Ying Zou; Wei Wang; Qingmei Zheng; Ying Feng; Zhangyun Tan; Xiaoqin Zeng; Yinqing Zhao; et al. (Clinical and Experimental Obstetrics & Gynecology)
Background: To explore the needs of obstetricians and gynecologists (OB-GYNs) for training methods and contents, under China’s three-level diagnosis and treatment system. Methods: Epidemiological investigation was adopted, and network questionnaires were distributed in the largest academic training platform of obstetrics and gynecology in China, from April 2020 to May 2020. The investigation contents mainly included training methods and contents of continuing medical education (CME), as well as the mastery of diseases by doctors from hospitals at different levels of training. Results: The questionnaire received a total of 16,400 cumulative page views. 4458 questionnaires were collected in total, and 3954 questionnaires were included in the research. Doctors from hospitals at different levels chose the professional direction of gynecological endocrine diseases as the subject requiring the most strengthening of training, with ratios of 80.47%, 81.60% and 82.10%, respectively. Abnormal uterine bleeding (AUB) was the most desirable training content for doctors from primary, secondary, and other hospitals, while training of polycystic ovary syndrome (PCOS) was mostly needed by doctors from tertiary hospitals. According to the investigation, network education was the major training form favored by doctors, as well as a preferential way to acquire professional resources. The number of doctors selecting site meeting report only took up 4.70%. Based on the single-factor chi-square (χ2) analysis of the degree of mastery of 19 diseases, significant statistical differences were found among doctors from hospitals at each level, except for birth control (p < 0.001). After related factors were corrected, the multivariate regression analysis indicated that the degree of mastery of diseases was positively correlated to hospital levels. Conclusions: Doctors from hospitals at each level failed to effectively master gynecological endocrine diseases, and AUB, menopausal syndrome, and PCOS were confirmed as diseases for which the doctors had the greatest need of continuing education.